Percutaneous Mechanical Thrombectomy for Acute Limb Ischemia With Aorto-iliac Occlusion - Yang, Xinrui; Li, Xiangxiang; Yin, Minyi; Wang, Ruihua; Ye, Kaichuang; Lu, Xinwu; Li, Weimin; Cheng, Yong; Qin, Jinbao (Frontiers in Surgery, 2022)
Background To evaluate the outcomes of percutaneous mechanical thrombectomy (PMT) with Rotarex catheter in patients with acute lower limb ischemia (ALI) caused by aorto-iliac occlusion. Materials and Methods Data of patients with ALI caused by aorto-iliac occlusion in our institutions from January 2010 and April 2020 were reviewed. The primary end point was limb salvage rate. The secondary end points included technical success rate, survival rate, complications after the operation and during the follow-up. Results A total of 85 patients with ALI was diagnosed with aorto-iliac occlusion. Thirty-eight patients were treated by PMT with Rotarex catheter and enrolled in present study. Twenty-four were male (63.2%), and 14 were female (36.8%). The mean age was 66 years (range 28–83). All 38 patients were treated with PMT, with additional catheter directed thrombolysis (2/38, 5.3%), balloon angioplasty (8/38, 21.1%) and stent deployment (7/38, 18.4%). The mean procedure time was 123 ± 31 min. Seven patients (18.4%) underwent continuous renal replacement therapy. Two patients received major amputations (above the knee) and 2 patients died for renal insufficiency and heart failure during the hospital stay. Thirty-day survival rate was 94.7% and limb salvage was 94.4%. The mean follow-up time was 14.0 months (8–22 months). There was no major amputation and target artery occlusion occurred during the follow-up period. Conclusion PMT with Rotarex catheter could be new option for acute aorto-iliac occlusion, leading to safe and effective results.